Efficient elimination of pancreatic cancer stem cells by hedgehog/GLI inhibitor GANT61 in combination with mTOR inhibition. Issue 1 (December 2016) - Miyazaki, Yumi; Matsubara, Shyuichirou; Ding, Qiang; Tsukasa, Koichiro; Yoshimitsu, Makoto; Kosai, Ken-ichiro; Takao, Sonshin
Abstract Background Pancreatic cancer is one of the most lethal malignancies. The innovative treatments are required and now the cancer stem cells (CSCs) are expected to be an effective target for novel therapies. Therefore we investigated the significance of hedgehog (Hh) signaling in the maintenance of CSC-like properties of pancreatic cancer cells, in order to discover the key molecules controlling their unique properties. Methods Human pancreatic cancer cell lines, Capan-1, PANC-1, MIA PaCa-2 and Capan-1 M9 were used for our experiments in DMEM/F12 medium containing 10 % fetal bovine serum. Sphere formation assay, immunofluorescence staining, flow cytometric analysis and MTT cell viability assay were performed to investigate molecular signals and the efficacy in the treatment of pancreatic cancer cells. Results Inhibition of the Hh pathway significantly reduced the expression of stem cell marker CD133 and sphere formation, an index of self-renewal capacity, demonstrating the suppression of CSC-like properties. Moreover, the GLI inhibitor GANT61 induced greater reduction in sphere formation and cell viability of pancreatic cancer cells than the smoothened (SMO) inhibitor cyclopamine. This suggests that GLI transcription factors, but not SMO membrane protein, are the key molecules in the Hh pathway. The treatment using GANT61 in combination with the inhibition of mTOR, which is another key molecule in pancreatic CSCs, resulted in the efficient reduction of cell viability and sphere formation of an inhibitor-resistant cell line, showing the strong efficacy and wide range applicability to pancreatic CSC-like cells. Conclusions Thus, this novel combination treatment could be useful for the control of pancreatic cancer by targeting pancreatic CSCs. This is the first report of the efficient elimination of pancreatic cancer stem-like cells by the double blockage of Hh/GLI and mTOR signaling.